Gambaran Perilaku Bullying Verbal Pada Siswa Sekolah Dasar : Literature Review - Indah Pratiwi; Herlina Herlina; Gamya Tri Utami (Jurnal Keperawatan, 2021)
Verbal bullying is a common bullying and it can be a trigger for other bullying. Study aims of study to determine the description of verbal bullying behavior in elementary school students. Design of this study used a literature review. There are some tools used to find related articles such as google scholar, PubMed, Plos One, and science direct with the keywords verbal bullying and elementary school students in 2016-2020 period. The research was conducted in 6 different countries such as Australia, Philippines, Brazil, Indonesia, Turkey and Spain. Majority of respondents who took part in the study were female (51%), grade 3 (31.5%) with age range of 8-9 years (25%). The results of the description of the prevalence of verbal bullying showed that there were more victims of verbal bullying (95.1%) with female students as victims (55.9%). A common form of verbal bullying is insulting or humiliating (30.7%). The assumption they bully is because of the physical appearance/smell of their friends (49.9%). The impacts that occurs on students as victims of verbal bullying: decrease in learning achievement (40%); poor mental health (40%). Verbal bullying can impacts school-age children to experience decreased learning achievement and poor mental health.